Indigenous peoples’ rights and the multicultural approach: For a twin-track dialogue between Canada and the Inter-American Human Rights System - Cerqueira, Daniel (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2022)
This article addresses the importance of a twin-track dialogue between Canada and the Inter-American Human Rights System (IAHRS), particularly with regards to the rights of Indigenous peoples. It describes how Canada has engaged with the IAHRS as a major financial and diplomatic supporter, while at the same time resisting full adherence to American Convention on Human Rights, its protocols and other regional instruments. The article also examines the influence that Canada’s multicultural approach of addressing national and ethnical differences has had in Latin America and in the IAHRS standards on the rights of Indigenous peoples. Finally, it maintains that the IAHRS has acknowledged states’ obligations that could inspire Canadian efforts to implement the United Nations Declaration on the Rights of Indigenous Peoples and reconcile with Indigenous nations.